EFEKTIVITAS PROYEK CAPACITY BUILDING FOR RESTORATION OF ECOSYSTEM IN CONSERVATION AREAS (RECA) DI TN. SEMBILANG TAHUN 2010-2015 - Tri Wijayaningsih; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research will explain about Effectiveness Project Capacity Building for Restoration of ecosystem in Conservation Areas (RECA) Performed by Japan International Cooperation Agency (JICA) with Indonesia on 2010-2015 in five Conservation areas that is National park of Sembilang, National park of Ciremai Mountain, National Park of Bromo Tengger Semeru, National Park of Merapi Mountain and National Park of Maneupeu Tanah Daru. In this research focus on Effectiveness Project Capacity Buiding for Restoration of Ecosystem in Conservation Areas (RECA) in National Park of Sembilang the problem occur is degradation mangrove caused Fish Pond Activity by the Community.Sources were obtained through literature review from Jurnals, Books, Thesis, reports, Internet and Guideline Project JICA-RECA to explain Project-RECA and analyzing Efectivty Project. The Perspektif used in this research is Green Thought and the Theories is Ekosentrism (Deep Ecology) and Effectiveness.In this research author concludes that Project-RECA in National Park of Sembilang Effektive as goals project analyzed by effektiviness theory. Project ouput in National park of Sembilang is 200,75 ha restoration land is success by planting mangrove seeds, 80% mangrove already grow well in degradation land in National Park of Sembilang Palembang, South Sumatera.Keywords : Japan International Cooperation Agency (JICA), Restoration Project, degradation Mangrove